The Role of Multimodality Imaging for Percutaneous Coronary Intervention in Patients With Chronic Total Occlusions - Melotti, Eleonora; Belmonte, Marta; Gigante, Carlo; Mallia, Vincenzo; Mushtaq, Saima; Conte, Edoardo; Neglia, Danilo; Pontone, Gianluca; Collet, Carlos; Sonck, Jeroen; Grancini, Luca; Bartorelli, Antonio L.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background Percutaneous coronary intervention (PCI) of Chronic total occlusions (CTOs) has been traditionally considered a challenging procedure, with a lower success rate and a higher incidence of complications compared to non-CTO-PCI. An accurate and comprehensive evaluation of potential candidates for CTO-PCI is of great importance. Indeed, assessment of myocardial viability, left ventricular function, individual risk profile and coronary lesion complexity as well as detection of inducible ischemia are key information that should be integrated for a shared treatment decision and interventional strategy planning. In this regard, multimodality imaging can provide combined data that can be very useful for the decision-making algorithm and for planning percutaneous CTO recanalization. Aims The purpose of this article is to appraise the value and limitations of several non-invasive imaging tools to provide relevant information about the anatomical characteristics and functional impact of CTOs that may be useful for the pre-procedural assessment and follow-up of candidates for CTO-PCI. They include echocardiography, coronary computed tomography angiography (CCTA), nuclear imaging, and cardiac magnetic resonance (CMR). As an example, CCTA can accurately delineate CTO location and length, distal coronary bed, vessel tortuosity and calcifications that can predict PCI success, whereas stress CMR, nuclear imaging and stress-CT can provide functional evaluation in terms of myocardial ischemia and viability and perfusion defect extension.